Can TERT rs2853669 polymorphysm indicate fibrosis in sarcoidosis? Telomerase polymorphism in sarcoidosis - Kement, Sümeyye; Turgut Ugurtay, Eda; Tanrıvermis Sayıt, Aslı; Tascı, Pınar; Unsal, Meftun (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2023)
Background and aim: Sarcoidosis is a systemic inflammatory disease of unknown cause, characterized by the presence of non-caseating granulomas, which can affect all organs in the body, especially the lung. The fibrotic stage 4 of sarcoidosis usually does not respond adequately to treatment and may cause respiratory distress in the patient. Some telomerase gene polymorphisms have been significantly associated with lung cancer and idiopathic pulmonary fibrosis. In our study, we aimed to investigate the relationship between telomerase mutation and progression to fibrosis in patients with sarcoidosis.Methods: A total of 93 patients, including 18 males and 73 females, who were clinically and histopathologically diagnosed with sarcoidosis were included in the study. The 78 patients included in the study were classified as non-fibrotic and 15 as fibrotic sarcoidosis. In telomerase rs2853669 single nucleotide polymorphism, three genotypes, homozygous TT, homozygous CC and heterozygous TC, were determined as the genotypes of the patients.Results: When non-fibrotic and fibrotic sarcoidosis groups were compared, no significant difference was found in terms of genotypes (p=0.76).  The FEV1 (forced expiratory volume in the first second) % of the CC genotype was lower than that of the other genotypes (p=0.01).Conclusions: In sarcoidosis patients, telomerase rs2853669 polymorphism does not indicate progression to fibrosis, but since FEV1% was found to be lower in individuals with homozygous CC polymorphism, it is thought that it may predict loss of respiratory function. Further studies are needed to evaluate the association of telomerase polymorphisms with fibrosis in sarcoidosis.